Negative electrode sheet, electrochemical device, and electronic device
Patent Information
- Application Number
- CN202510463085.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-20
AI Technical Summary
现有技术中,通常使用石墨与硅材料进行匹配来降低膨胀,而石墨材料的杨氏模量通常在10~15GPa,与硅材料匹配涂布冷压形成负极活性材料层后,由于在循环过程中硅材料的体积膨胀较大,硅材料体积膨胀释放应力会导致杨氏模量较低的石墨材料发生形变,弱化了石墨材料与硅材料的连接,随着硅材料持续膨胀收缩负极极片结构完整性遭到破坏甚至脱膜,导致部分硅材料电连接失效,电芯循环性能表现为衰减加速,膨胀失控
[0025]本申请提供了一种负极极片、电化学装置及电子装置。本申请的负极极片包括负极集流体和设置于负极集流体的至少一个表面上的负极活性材料层,负极活性材料层的杨氏模量为E0且满足:40GPa≤E0≤80GPa;负极活性材料层包含第一负极活性材料和第二负极活性材料,其中,第二负极活性材料的杨氏模量为E2且满足:30GPa≤E2≤50GPa。本申请选用高杨氏模量的第二负极活性材料与第一负极活性材料进行匹配,通过调控第二负极活性材料以及负极活性材料层的杨氏模量在本申请范围内,电化学装置在循环过程中,第一负极活性材料的膨胀收缩导致第二负极活性材料受到挤压,高杨氏模量的第二负极活性材料的形变是可逆的,有利于高杨氏模量的第二负极活性材料在循环中始终与第一负极活性材料保持连接,有利于缓解第一活性材料的电连接失效,维持负极极片结构的完整性,有利于电化学装置循环性能的提升。
Smart Images

Figure BDA0005357780990000161 
Figure BDA0005357780990000171 
Figure BDA0005357780990000181
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical technology, and in particular to a negative electrode, an electrochemical device, and an electronic device. Background Technology
[0002] With the rapid development of modern technology, the demand for high-performance energy storage devices is increasing in fields such as portable electronic devices and electric vehicles. Lithium-ion batteries, as a highly efficient and environmentally friendly energy storage device, have been widely used in many fields due to their advantages such as high energy density, long cycle life, and low self-discharge rate. As lithium-ion batteries continue to develop, the performance requirements for batteries are becoming increasingly stringent.
[0003] Silicon has a theoretical specific capacity as high as 4200 mAh / g, making it a promising material for lithium-ion batteries. However, during charge-discharge cycles, silicon undergoes a 300% volume expansion due to the insertion and extraction of lithium ions. Current technologies typically use graphite to match silicon to reduce this expansion. Graphite's Young's modulus is usually between 10 and 15 GPa. After being coated and cold-pressed with silicon to form the negative electrode active material layer, the significant volume expansion of silicon during cycling causes stress release, leading to deformation of the graphite with its lower Young's modulus. This weakens the connection between graphite and silicon. As silicon continues to expand and contract, the integrity of the negative electrode structure is compromised, potentially resulting in delamination or even detachment. This leads to partial failure of the silicon's electrical connections, resulting in accelerated cell degradation and uncontrolled expansion during battery cycle performance. Summary of the Invention
[0004] This application aims to provide a negative electrode, an electrochemical device, and an electronic device, with the goal of reducing the expansion of silicon-containing negative electrodes and improving cycle performance.
[0005] In a first aspect, this application proposes a negative electrode sheet, which includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector, wherein the Young's modulus of the negative active material layer is E0 and satisfies: 40GPa≤E0≤80GPa.
[0006] The negative electrode active material layer includes a first negative electrode active material and a second negative electrode active material, wherein the Young's modulus of the second negative electrode active material is E2 and satisfies: 30GPa≤E2≤50GPa.
[0007] In the above technical solution, regulating E0 within the above range is beneficial for adapting to the stress changes of the negative electrode sheet during the charge-discharge cycle, maintaining the structural stability of the negative electrode sheet, and further improving the cycle performance of the electrochemical device; regulating E2 within the above range is beneficial for maintaining sufficient contact with the first negative electrode active material, conductive agent and binder and participating in the electrochemical reaction, and for easily maintaining the integrity of the conductive network during the cycle of the electrochemical device, further improving the cycle performance of the electrochemical device.
[0008] According to the negative electrode sheet of the first aspect, based on the total mass of the negative electrode active material, the mass percentage of the first negative electrode active material is W1, the mass percentage of the second negative electrode active material is W2, and satisfies: 0.25≤W1 / W2≤4.
[0009] According to the negative electrode plate in the first aspect, W1 and W2 satisfy: 0.5≤W1 / W2≤2.
[0010] In the above technical solution, adjusting W1 / W2 within the above range is beneficial to controlling the expansion and contraction rate of the negative electrode active material during cycling, making it easier for the conductive network of the negative electrode active material layer to maintain electrical connection during cycling, and having a high specific capacity of the material layer.
[0011] According to the negative electrode sheet of the first aspect, the average particle size of the first negative electrode active material is D1, the average particle size of the second negative electrode active material is D2, and satisfies: 0.75≤D2 / D1≤1.25.
[0012] In the above technical solution, by adjusting D2 / D1 within the above range, the particle sizes of the first negative electrode active material and the second negative electrode active material are matched with each other, which is beneficial to improve the compaction density, thereby increasing the mutual contact between particles, thereby improving the stability of the negative electrode structure, thereby improving the specific capacity of the material layer, improving the cycle performance of the electrochemical device, and reducing the expansion rate of the electrochemical device.
[0013] According to the negative electrode plate of the first aspect, D1 and D2 satisfy: 4μm≤D1≤12μm, and / or 3μm≤D2≤15μm.
[0014] In the above technical solution, by adjusting D1 and D2 within the above range, the average particle size of the negative electrode active material is within a suitable range, which is conducive to good contact between the first negative electrode active material and the second negative electrode active material. While facilitating lithium ion transport, it is also conducive to reducing electrolyte consumption, increasing compaction density, and thus improving the cycle performance of the electrochemical device.
[0015] According to the negative electrode plate in the first aspect, 25% ≤ W1 ≤ 80%.
[0016] In the above technical solution, it is beneficial to control E0 within the aforementioned range, thereby alleviating volume expansion and improving the structural stability of the negative electrode and the specific capacity of the material layer, thus improving the cycle performance of the electrochemical device and reducing the expansion rate of the electrochemical device.
[0017] According to the negative electrode sheet of the first aspect, the first negative electrode active material is one or more of silicon-carbon materials, silicon-oxygen materials, and elemental silicon materials.
[0018] According to the negative electrode sheet of the first aspect, the second negative electrode active material is selected from MCMB and / or lithium titanate.
[0019] According to the negative electrode sheet of the first aspect, the negative electrode active material layer also includes a negative electrode binder, and the film elongation of the negative electrode binder is 40% to 500%.
[0020] In the above technical solution, controlling the film stretching ratio of the negative electrode binder within the above range is beneficial to maintaining the connection between particles when the negative electrode active material undergoes large deformation during charging and discharging, thereby helping the negative electrode sheet to maintain structural integrity and improving the structural stability of the negative electrode sheet.
[0021] According to the negative electrode sheet of the first aspect, the negative electrode binder is selected from one or more of styrene-butadiene rubber, polyurethane, polyimide, polyamide-imide, polyvinylidene fluoride, and polyvinylbenzene.
[0022] In a second aspect, this application proposes an electrochemical device comprising a positive electrode, a separator, an electrolyte, and a negative electrode as described in any embodiment of the first aspect above, wherein the separator is located between the positive electrode and the negative electrode.
[0023] Thirdly, this application proposes an electronic device comprising an electrochemical device as described in any embodiment of the second aspect above.
[0024] The beneficial effects of this application are:
[0025] This application provides a negative electrode sheet, an electrochemical device, and an electronic device. The negative electrode sheet of this application includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector. The Young's modulus of the negative active material layer is E0 and satisfies: 40 GPa ≤ E0 ≤ 80 GPa. The negative active material layer includes a first negative active material and a second negative active material, wherein the Young's modulus of the second negative active material is E2 and satisfies: 30 GPa ≤ E2 ≤ 50 GPa. This application selects a second negative electrode active material with a high Young's modulus to match the first negative electrode active material. By adjusting the Young's modulus of the second negative electrode active material and the negative electrode active material layer within the scope of this application, during the cycling process of the electrochemical device, the expansion and contraction of the first negative electrode active material causes the second negative electrode active material to be compressed. The deformation of the second negative electrode active material with a high Young's modulus is reversible, which is beneficial for the second negative electrode active material with a high Young's modulus to always maintain connection with the first negative electrode active material during cycling. This helps to alleviate the electrical connection failure of the first active material, maintain the integrity of the negative electrode structure, and improve the cycling performance of the electrochemical device.
[0026] Additional aspects and advantages of the embodiments of this application will be described, shown, or illustrated in part by way of implementation of the embodiments of this application in the following description. Attached Figure Description
[0027] One or more embodiments are illustrated by way of example with reference to the accompanying drawings, and these illustrative examples are not intended to limit the embodiments.
[0028] Figure 1 SEM image of the negative electrode sheet prepared in Example 1-1 of this application;
[0029] Figure 2 This is a SEM image of the negative electrode sheet prepared in Comparative Example 3 of this application. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of this application, but not all embodiments.
[0031] In this application, the reference to "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.
[0032] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0033] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0034] The technical features involved in the different embodiments of this application described below can be combined with each other as long as they do not conflict with each other.
[0035] As used in this application, "Young's modulus" is the ratio of unit strain to unit stress in a material under tension, i.e., Young's modulus E is equal to the ratio of stress σ to strain ε: E = ε / σ. Where σ represents the force per unit area of the material under tension, and ε represents the linear change per unit length.
[0036] As used in this application, "silicon-carbon material" refers to a silicon-carbon composite material, wherein the mass percentage of silicon is 30% to 70% and the mass percentage of carbon is 30% to 70% based on the mass of the silicon-carbon composite material. This application does not impose any particular limitation on the silicon-carbon composite material, as long as it achieves the purpose of this application. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be silicon material deposited on a carbon skeleton, or carbon material deposited on a silicon skeleton. Silicon-carbon composite materials are materials that significantly improve the capacity and electrochemical performance of anode materials by doping silicon materials with carbon materials of different structures. They are beneficial for the insertion and extraction of large amounts of lithium ions during the charging and discharging process of electrochemical devices and can be used as anode materials for electrochemical devices. Exemplarily, for silicon-carbon materials with silicon material deposited on a carbon skeleton, its expansion rate is mainly affected by the silicon content in the silicon-carbon material, and its Young's modulus is mainly affected by the mass percentage of silicon, the strength of the carbon skeleton, and the porosity of the carbon skeleton. Silicon-oxygen materials include SiOx, where 0 < x < 2. For example, silicon-oxygen materials may include silicon suboxide (SiO, with a silicon to oxygen molar ratio of 1:1) or SiO2. 1.2 (The molar ratio of silicon to oxygen is 1:1.2). For example, the Young's modulus of silicon-oxygen materials can be adjusted by regulating the molar ratio of silicon to oxygen and the porosity. Elemental silicon materials include micron-sized silicon, nano-sized silicon, etc. For example, the Young's modulus of elemental silicon materials can be adjusted by regulating the porosity of the silicon material.
[0037] As used in this application, "MCMB" is short for Mesocarbon Microbeads. MCMB is a micron-sized spherical carbon material produced by the thermal condensation reaction of pitch compounds during specific high-temperature processing. It has a nematic liquid crystal layered stacked structure and is a micron-sized spherical carbon material refined from complex pitch raw materials. Exemplarily, the Young's modulus and expansion coefficient of MCMB are mainly affected by the material's processing technology.
[0038] In a first aspect, this application provides a negative electrode sheet, which includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector. The Young's modulus of the negative active material layer is E0 and satisfies: 40 GPa ≤ E0 ≤ 80 GPa. For example, E0 can be 5 GPa, 10 GPa, 15 GPa, 20 GPa, 30 GPa, 40 GPa, 50 GPa, 60 GPa, 70 GPa, 80 GPa, or a range of any two of the above values; further, 50 GPa ≤ E0 ≤ 70 GPa.
[0039] The negative electrode active material layer includes a first negative electrode active material and a second negative electrode active material, wherein the Young's modulus of the second negative electrode active material is E2 and satisfies: 30GPa≤E2≤50GPa. For example, E2 can be 30GPa, 35GPa, 40GPa, 45GPa, 50GPa or a range of any two of the above values.
[0040] When the Young's modulus E0 of the negative electrode active material layer is less than 40 GPa, the second active material is prone to slip deformation, leading to uneven binder distribution, damage to the bonding network, and further resulting in excessively high local current density, causing overcharging or over-discharging and accelerating capacity decay. When the Young's modulus E0 of the negative electrode active material layer is greater than 80 GPa, the compaction density of the negative electrode sheet is low, resulting in energy density loss, and it is also prone to poor interfacial contact between the negative electrode sheet and the current collector, thereby increasing interfacial impedance and affecting the cycle performance of the electrochemical device. When the Young's modulus of the negative electrode material layer is within the range of this application, it can effectively adapt to the stress changes of the negative electrode sheet during charge-discharge cycles, which is beneficial to maintaining the structural stability of the negative electrode sheet and further improving the cycle performance of the electrochemical device.
[0041] When the Young's modulus E2 of the second negative electrode active material is greater than 50 GPa, insufficient contact between it and the first negative electrode active material, conductive agent, and binder can prevent some active material from fully participating in the electrochemical reaction, thus reducing the specific capacity of the material layer. When the Young's modulus E2 of the second negative electrode active material is less than 30 GPa, the second active material is prone to deformation, which may lead to the destruction of the conductive network and the failure of the electrical connection of the first negative electrode active material. This further damages the integrity of the negative electrode structure, affecting the integrity of the conductive network of the negative electrode active material layer, which is detrimental to the specific capacity of the material layer and leads to a decrease in cycle performance. When the Young's modulus of the second negative electrode active material is within the range of this application, it is easier to maintain sufficient contact with the first negative electrode active material, conductive agent, and binder and participate in the electrochemical reaction. Moreover, it is easier to maintain the integrity of the conductive network during the cycling process of the electrochemical device, further improving the cycle performance of the electrochemical device.
[0042] In some implementations, based on the total mass of the negative electrode active materials, the mass percentage of the first negative electrode active material is W1, the mass percentage of the second negative electrode active material is W2, and the following condition is met: 0.25≤W1 / W2≤4. For example, W1 / W2 can be 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3, 3.5, 4, or a range of any two of the above values.
[0043] In some embodiments of this application, W1 and W2 satisfy: 0.5 ≤ W1 / W2 ≤ 2.
[0044] Based on the total mass of the negative electrode active material, when the ratio of the mass percentage of the first negative electrode active material W1 to the mass percentage of the second negative electrode active material W2, W1 / W2 < 0.5, especially W1 / W2 < 0.25, the content of the first negative electrode active material is too low, affecting the specific capacity of the material layer. When the ratio of the mass percentage of the first negative electrode active material W1 to the mass percentage of the second negative electrode active material W2, W1 / W2 > 2, especially W1 / W2 > 4, the content of the second negative electrode active material is too low. During cycling, the negative electrode active material is prone to significant expansion and contraction, which can easily lead to the failure of the electrical connection of the negative electrode active material, thereby affecting the specific capacity of the material layer and the cycling performance and expansion rate of the electrochemical device. Adjusting W1 / W2 within the above range is beneficial to controlling the expansion and contraction rate of the negative electrode active material during cycling, making it easier for the conductive network of the negative electrode active material layer to maintain electrical connection during cycling, and also resulting in a higher specific capacity of the material layer.
[0045] In some implementations, 25% ≤ W1 ≤ 80%, for example, W1 can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or a range of any two of the above values.
[0046] When the mass percentages of the first and second negative electrode active materials are within the range specified in this application, E0 can be controlled within the aforementioned range, which can alleviate volume expansion and improve the structural stability of the negative electrode sheet and the specific capacity of the material layer, thereby improving the cycle performance of the electrochemical device and reducing the expansion rate of the electrochemical device.
[0047] In some embodiments of this application, the average particle size of the first negative electrode active material is D1, and the average particle size of the second negative electrode active material is D2, satisfying: 0.75≤D2 / D1≤1.25. For example, D2 / D1 can be 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, 1.25, or a range of any two of the above values.
[0048] When the average particle size difference between the first and second negative electrode active materials is too large, it may lead to uneven dispersion of the active materials in the negative electrode active material layer, resulting in uneven local current density distribution within the negative electrode sheet, accelerating capacity decay, and affecting the cycle performance of the electrochemical device. Furthermore, an excessively large difference in average particle size may also cause uneven stress distribution and volume expansion of the negative electrode sheet during charging and discharging, leading to cracking and localized delamination, affecting the structural stability of the negative electrode sheet and increasing the risk of internal short circuits and thermal runaway. Within the aforementioned range, matching the particle sizes of the first and second negative electrode active materials is beneficial for increasing compaction density, thereby increasing interparticle contact, improving the structural stability of the negative electrode sheet, enhancing the specific capacity of the material layer, improving the cycle performance of the electrochemical device, and reducing the expansion rate of the electrochemical device.
[0049] In some embodiments of this application, D1 and D2 satisfy: 4μm≤D1≤12μm, and / or 3μm≤D2≤15μm. For example, D1 can be 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or a range of any two of the above values, and D2 can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or a range of any two of the above values.
[0050] Setting D1 and D2 within the aforementioned range ensures that the average particle size of the negative electrode active material is within a suitable range, thereby enabling good contact between the first and second negative electrode active materials. This facilitates lithium-ion transport, reduces electrolyte consumption, increases compaction density, and ultimately improves the cycle performance of the electrochemical device.
[0051] In this application, negative electrode active materials with different average particle sizes can be purchased, and their average particle size can be tested using scanning electron microscopy to select the negative electrode active material with the desired particle size. When testing the average particle size, the average value of the diameter of the largest circumscribed circle of 10 particles is selected as the average particle size.
[0052] In this application, the expansion rate of the first negative electrode active material is greater than that of the second negative electrode active material. In particular, in some embodiments, the expansion rate of the first negative electrode active material is α1 and 130% ≤ α1 ≤ 350%. For example, α1 can be 130%, 150%, 180%, 200%, 250%, 300%, 350%, or a range of any two of the above values. The expansion rate of the second negative electrode active material is α2 and 0 ≤ α2 ≤ 10%. For example, α2 can be 0%, 1%, 2%, 5%, 8%, 10%, or a range of any two of the above values.
[0053] In this application, setting α1 and α2 within the above-mentioned range allows the expansion rates of the two negative electrode active materials to match each other, improving the structural stability of the negative electrode sheet. Moreover, during cycling, it facilitates the first negative electrode active material and the second negative electrode active material to maintain good contact, thereby improving the cycling performance of the electrochemical device and mitigating expansion.
[0054] In particular, in some specific implementations, the expansion rate of the first negative electrode active material is 180% ≤ α1 ≤ 260%, which can further control the expansion of the first negative electrode active material during cycling, thereby facilitating the maintenance of good conductivity of the conductive network in the negative electrode active material layer, thus enabling the electrochemical device to have a high capacity retention rate and low expansion.
[0055] It is understood that the adjustment of α1 can be achieved as long as it meets the purpose of this application. For example, α1 can be adjusted by adjusting the mass percentage of silicon in the silicon-carbon material. The adjustment of α2 can also be achieved as long as it meets the purpose of this application. For example, α2 can be adjusted by adjusting the graphitization degree of MCMB.
[0056] In some embodiments, the Young's modulus of the first negative electrode active material is E1 and satisfies E1 > 50 GPa. Preferably, 50 GPa < E1 ≤ 100 GPa. For example, E1 can be 51 GPa, 55 GPa, 60 GPa, 70 GPa, 80 GPa, 90 GPa, 100 GPa, or a range of any two of the above values.
[0057] Because the expansion rate of the first negative electrode active material is relatively large, it is prone to large deformation during charging and discharging. When the Young's modulus of the second negative electrode active material is low, the stress released by the volume expansion of the first negative electrode active material can easily lead to deformation of the second negative electrode active material with a lower Young's modulus, thereby weakening the connection between the first and second negative electrode active materials and generating interface defects. By controlling the Young's modulus of the second negative electrode active material and the negative electrode active material layer within the scope of this application, the second negative electrode active material with a low Young's modulus can always maintain connection with the first negative electrode active material during cycling, which is beneficial to improving expansion, enhancing the structural stability of the negative electrode sheet, and improving the cycle performance of the electrochemical device.
[0058] It is understood that the adjustment of E1 only needs to achieve the purpose of this application, for example, it can be adjusted by means of silicon mass percentage, porosity, etc. The adjustment of E2 only needs to achieve the purpose of this application, for example, it can be adjusted by means of MCMB processing temperature, time, etc. The adjustment of E0 only needs to achieve the purpose of this application, for example, it can be adjusted by means of adjusting the ratio of E1, E2 and the first and second negative electrode active materials, etc.
[0059] In some implementations, the first negative electrode active material is a silicon-containing material, preferably a silicon-carbon material, a silicon-oxygen material, and / or a silicon-elemental material.
[0060] In some specific implementations, the mass percentage of silicon in the first negative electrode active material is 30% to 60%. For example, the mass percentage of silicon in the first negative electrode active material can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a range consisting of any two of the above values.
[0061] By controlling the mass percentage of silicon in the first negative electrode active material to be between 30% and 60%, it is beneficial to improve the energy density of the electrochemical device, and to regulate the expansion rate of the first negative electrode active material within the aforementioned range, thereby improving the cycle performance of the electrochemical device.
[0062] In some implementations, the first negative electrode active material is a silicon-carbon material.
[0063] In some implementations, the second negative electrode active material is selected from MCMB and / or lithium titanate.
[0064] Compared with traditional graphite anode materials, MCMB and lithium titanate materials have higher Young's modulus, which makes it easier to maintain a good connection with the first anode active material during cycling, even when the first anode active material undergoes large deformation during charging and discharging. This improves the structural stability of the anode sheet and the cycle performance of the electrochemical device.
[0065] In some embodiments, the negative electrode active material layer also includes a negative electrode binder, the adhesive film elongation of which is 40% to 500%, for example, 40%, 50%, 80%, 100%, 200%, 300%, 400%, 500%, or any combination of two of the above values.
[0066] Furthermore, the film elongation of the negative electrode adhesive is 100% to 500%, for example, it can be 100%, 200%, 300%, 400%, 500%, or a range of any two of the above values.
[0067] This application selects a tough binder and sets the film stretch ratio of the negative electrode binder to be between 40% and 500%. This makes it less prone to breakage after the first negative electrode active material expands, facilitating the maintenance of interparticle connections and thus helping the negative electrode sheet maintain structural integrity, thereby improving the structural stability of the negative electrode sheet. Furthermore, the film stretch ratio of the negative electrode binder is between 100% and 500%. When the film stretch ratio is too low, the film binds the active material more strongly, but insufficient stretching easily leads to the breakage of the negative electrode active material layer, thereby destroying the bonding network and the conductive network, affecting the cycle performance of the electrochemical device. When the film stretch ratio is too high, the ion transport impedance in the negative electrode active material layer is high, leading to difficulties in lithium removal, which also affects the cycle performance of the electrochemical device.
[0068] In some embodiments, the negative electrode binder is selected from one or more of styrene-butadiene rubber, polyurethane, polyimide, polyamide-imide, polyvinylidene fluoride, and polyvinylbenzene.
[0069] In some specific implementations, the weight-average molecular weight of the negative electrode binder is 30,000 g / mol to 400,000 g / mol, for example, it can be 30,000 g / mol, 40,000 g / mol, 50,000 g / mol, 80,000 g / mol, 100,000 g / mol, 150,000 g / mol, 200,000 g / mol, 250,000 g / mol, 300,000 g / mol, 350,000 g / mol, or 400,000 g / mol.
[0070] This application sets the weight-average molecular weight of the negative electrode binder within the aforementioned range, so that the elongation of the negative electrode binder film is within the aforementioned range, thereby facilitating the maintenance of the connection between the negative electrode active material particles.
[0071] In some specific implementations, the negative electrode active material layer also includes a conductive agent, which is preferably one or more of the following: carbon nanotubes (single-walled carbon nanotubes, multi-walled carbon nanotubes), conductive carbon black, acetylene black (AB), Ketjen black (KB), graphite, carbon fiber, carbon nanotubes, graphene, amorphous carbon, hard carbon, soft carbon, glassy carbon, and carbon nanofibers.
[0072] In some specific implementations, based on the total mass of the negative electrode active material layer, the mass percentage of the negative electrode active material is 85-95%, the mass percentage of the negative electrode binder is 4.5-14%, and the mass percentage of the conductive agent is 0.5-1%. For example, the mass percentage of the negative electrode active material can be 85%, 88%, 90%, 92%, 95%, or any combination of two of the above values; the mass percentage of the negative electrode binder can be 4.5%, 5%, 6%, 8%, 10%, 12%, 14%, or any combination of two of the above values; and the mass percentage of the conductive agent can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any combination of two of the above values.
[0073] Optionally, the negative electrode active material layer may also contain a dispersant and / or a defoamer. The dispersant is preferably selected from one or more of the sodium, potassium, and ammonium salts of dioctyl sulfosuccinate, dipentyl sulfosuccinate, and dicyclopentyl sulfosuccinate. The defoamer is preferably selected from one or more of the following: fatty acid ester defoamers, alcohol defoamers, ether defoamers, phosphate ester defoamers, amine defoamers, amide defoamers, metal soap defoamers, sulfate ester defoamers, organosilicon defoamers, mineral oil defoamers, low molecular weight polyethylene glycol oleate, nonylphenol ethylene oxide low molar adduct, and prolonic type ethylene oxide low molar adduct.
[0074] In some specific implementations, the coating mass of the negative electrode active material layer is 1.5–7.5 mg / cm³. 2 The compaction density of the negative electrode active material layer is 1.0–1.75 g / cm³. 3 .
[0075] By setting the coating quality and compaction density of the negative electrode active material layer within the above range, the negative electrode sheet can have a higher capacity, which can improve the energy storage capacity of the electrochemical device, reduce the risk of negative electrode active material shedding, and thus improve the cycle performance of the electrochemical device.
[0076] In some embodiments, the specific capacity C1 of the first negative electrode active material is greater than the specific capacity C2 of the second negative electrode active material. Preferably, C1 and C2 satisfy: 800mAh / g≤C1≤3000mAh / g, 250mAh / g≤C2≤390mAh / g. For example, C1 can be 800mAh / g, 1000mAh / g, 1500mAh / g, 2000mAh / g, 2500mAh / g, 3000mAh / g, or any range of two of the above values, and C2 can be 250mAh / g, 280mAh / g, 300mAh / g, 320mAh / g, 350mAh / g, 370mAh / g, 390mAh / g, or any range of two of the above values.
[0077] If both the first and second negative electrode active materials are high-specific-capacity materials, significant volume expansion and contraction are likely to occur during lithium insertion / extraction, which can easily lead to electrical connection failure of the negative electrode active materials, affecting the specific capacity of the material layer and the cycle performance of the electrochemical device. If both are low-specific-capacity materials, the capacity will decrease, resulting in a loss of energy density. By setting the specific capacity of the first and second negative electrode active materials within the above-mentioned range, it is beneficial to improve expansion, enhance the structural stability of the negative electrode sheet, and improve the cycle performance of the electrochemical device.
[0078] It is understood that the specific capacity of the first and second negative electrode active materials described in this application refers to the capacity exerted per unit mass of the negative electrode active material in an electrochemical device, which is different from the theoretical specific capacity of the material itself. The specific capacity exerted by the material layer mentioned in this application refers to the specific capacity exerted by the negative electrode material layer. Calculating the mass of the active material on the positive electrode side, assuming that all lithium delithiation of the positive electrode active material is embedded in the negative electrode sheet, the measured discharge capacity is the capacity that the negative electrode sheet can exert. Since the electrode design may result in the negative electrode sheet size exceeding the positive electrode sheet size, using the mass of the positive electrode active material as a benchmark for calculation is more accurate. By testing the specific capacity exerted by the material layer, the capacity exertion capability of the negative electrode active material can be fed back, further reflecting the connection effect of the first and second negative electrode active materials.
[0079] Secondly, this application also provides an electrochemical device, including a positive electrode, a separator, an electrolyte, and a negative electrode, wherein the separator is located between the positive electrode and the negative electrode.
[0080] This application also proposes an electronic device, including the electrochemical device as described in the second aspect above. The electronic device in this application is not particularly limited and can be any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, Bluetooth headsets, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., while spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0081] Example
[0082] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0083] Test methods and equipment:
[0084] I. Sampling of the negative electrode:
[0085] The lithium-ion battery was discharged at a constant current of 0.5C to the discharge cutoff voltage at 25°C. The lithium-ion battery was then disassembled under an argon atmosphere, and the negative electrode sheet was soaked in dimethyl carbonate solvent for 2 hours and dried at 60°C for 1 hour to obtain the negative electrode sheet. The discharge cutoff voltage of the lithium-ion battery in the embodiments and comparative examples of this application is 3.0V. It is understood that when the voltage range marked on the battery packaging is 3.0V to 4.45V, the charging cutoff voltage is 4.45V and the discharging cutoff voltage is 3.0V. Unless otherwise specified, the charging cutoff voltage of the lithium-ion battery used as an example in this application is 4.45V and the discharging cutoff voltage is 3.0V.
[0086] Unless otherwise specified, the following test methods shall use the negative electrode sheet obtained by the above method for testing.
[0087] II. Testing Young's Modulus:
[0088] (1) Sampling of negative electrode sheet:
[0089] The negative electrode sheet was obtained by sampling according to the negative electrode sheet sampling method in Test Method 1;
[0090] (2) Take the negative electrode sheet from (1), measure the coating thickness S1 of the single-sided negative electrode sheet, and perform nanoindentation test using a nanoindenter with the device model HysitronTI 990TriboIndenter. The probe pressing speed is 1μm / second, and the load is applied until the displacement reaches S2, where S2=0.75*S1, and the Young's modulus E0 of the negative electrode active material layer is obtained.
[0091] (3) Take the negative electrode sheet from (1), ion cut to obtain the cross section of the negative electrode active material layer, use scanning electron microscopy to analyze the elemental composition of the negative electrode active material, use atomic force microscopy to measure the Young's modulus of the active particles in the negative electrode active material layer, select a contact probe and calibrate it, set the force curve parameters and locate the particles, collect multi-point force curves, and calculate the Young's modulus by fitting the Hertz model. Measure 16 times and take the average value to obtain E1 and E2.
[0092] III. Testing of the mass percentage of the first and second negative electrode active materials:
[0093] This can be obtained through testing using the following methods:
[0094] (1) The negative electrode is obtained by sampling according to the negative electrode sampling method in Test Method 1;
[0095] (2) Take the negative electrode active material layer powder from the negative electrode sheet in (1) and test the mass percentage content of silicon element;
[0096] (3) Based on the mass percentage of silicon in the first negative electrode active material measured by test method five, the mass percentage of the first negative electrode active material and the second negative electrode active material are calculated.
[0097] IV. Test of average particle size:
[0098] The average particle size can be obtained by testing the following methods:
[0099] 1) The negative electrode sheet is obtained by sampling according to the negative electrode sheet sampling method in Test Method 1. The negative electrode sheet is ion cut to obtain the cross-section. The cross-section is then used to distinguish the particles of the first negative electrode active material and the second negative electrode active material by scanning electron microscopy.
[0100] 2) The scanning electron microscope window includes the thickness of the negative electrode active material on one side. The maximum particle size of the negative electrode active material particles containing Si and those without Si is measured using a length measuring tool. Ten particles are taken from each particle and the average particle size is calculated.
[0101] V. Test of the mass percentage of silicon in the first negative electrode active material:
[0102] This can be obtained through testing using the following methods:
[0103] (1) The negative electrode is obtained by sampling according to the negative electrode sampling method in Test Method 1;
[0104] (2) Take the negative electrode sheet from (1), and ion cut it to obtain the cross-section of the negative electrode active material layer. Use a scanning electron microscope to perform elemental analysis on the first negative electrode active material particles, and take the average value of 10 particles to obtain the mass percentage of silicon.
[0105] VI. Test of film elongation:
[0106] According to GB / T 1040.3-2006, the tensile strength of adhesive film can be obtained by testing the following methods:
[0107] 1) Spread the adhesive evenly in the container and dry it to prepare a film. The standard film size used for testing in this application is 150mm×20mm×0.5mm (error ±0.2mm).
[0108] 2) Prepare dumbbell-shaped specimens in accordance with GB / T 1040.3-2006; the width, total length and gauge length of the specimens shall meet specific requirements.
[0109] 3) Use a thickness gauge (minimum scale 0.01 mm) to measure the thickness of each specimen and record the data; install the specimen on a universal testing machine and use a pneumatic clamp to fix the specimen to ensure that the specimen does not slip or move during the test; perform tensile testing according to the test procedure of GB / T 1040.1-2006, and record the maximum stress and elongation at fracture for each specimen.
[0110] 4) Calculate the tensile strength and elongation at break of each specimen according to the formula specified in GB / T 1040.1-2006.
[0111] VII. Test of material expansion rate:
[0112] The negative electrode sheet was sampled according to the sampling method in Test Method 1. The negative electrode sheet was immersed in deionized water and ultrasonically treated (40kHz, 30min). It was then centrifuged at 5000rpm for 5min to obtain the precipitate. After washing three times, it was vacuum dried. The first and second negative electrode active material single particles were separated under SEM using probe microscopy or microtweezers. The diameter of the negative electrode active material particles was measured using a scanning electron microscope. The connecting carbon fiber filament was placed in a saturated lithium hexafluorophosphate carbonate solution, and a lithium metal reference electrode was added to form a half cell. The negative electrode active material particles were discharged to 5mV, and the diameter of the particles after full lithium intercalation was measured again. The average value was taken after five repetitions. The volume expansion rate of the particles was calculated according to the quasi-spherical theory.
[0113] 8. Testing of the specific capacity of the material layer:
[0114] The battery, after being filled with electrolyte, is vacuum-sealed, left to stand, and formed (charged at 0.1C constant current to 3.4V, then charged at 1C constant current to 4.45V and charged at constant voltage to the cutoff current of 0.02C), and then discharged at 0.2C current to 3.0V to obtain the discharge capacity; the positive electrode active material mass is calculated as: positive electrode coating mass × single-layer coating area × number of positive electrode active material layers × positive electrode active material mass fraction (this application uses a stacked cell as an example).
[0115] The specific capacity of the material layer (mAh / g) = discharge capacity (mAh) / mass of positive electrode active material (g)
[0116] 9. Capacity retention rate after 800 laps
[0117] The specific testing method is as follows:
[0118] The lithium-ion battery was left to stand at 25°C for 60 minutes, then charged at a constant current rate of 0.5C to a full charge voltage of 4.45V. It was then charged further at a constant voltage of 4.45V until the cutoff current of 0.02C was reached. After standing for 5 minutes, it was discharged at a constant current rate of 0.5C to 3.0V. This constitutes one charge-discharge cycle. The discharge capacity of the first cycle was recorded. The lithium-ion battery was cycled 800 times using the same steps, and the discharge capacity after 800 cycles was recorded.
[0119] The capacity retention rate of a lithium-ion battery after 800 cycles = (discharge capacity after 800 cycles / discharge capacity of the first cycle) × 100%.
[0120] 10. Battery swelling rate after 800 cycles
[0121] The specific testing method is as follows:
[0122] At 25°C, the battery thickness was measured using a height gauge. The lithium-ion battery was charged at a constant current rate of 0.5C to a full charge voltage of 4.45V, then charged at a constant voltage of 4.45V until a cutoff current of 0.02C was reached, followed by a constant current discharge of 0.5C to 3V. This constituted the first cycle. The lithium-ion battery was subjected to 800 cycles under the above conditions, and the thickness at 4.45V after 800 cycles was measured using a height gauge. The expansion rate was calculated.
[0123] Expansion rate (%) = (thickness after cycle - thickness before cycle) / thickness before cycle × 100%.
[0124] Example 1-1
[0125] The negative electrode, positive electrode, and lithium-ion battery in this embodiment are prepared by the following method.
[0126] <Preparation of Negative Electrode Sheets>
[0127] The first negative electrode active material, silicon-carbon material (where silicon content is 50% by mass based on the mass of silicon-carbon material), the second negative electrode active material, MCMB, the negative electrode binder, styrene-butadiene rubber, and the conductive agent, single-walled carbon nanotubes, are mixed in a ratio of 45:45:9:1. Then, deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40%.
[0128] The negative electrode slurry was uniformly coated on both surfaces of the negative electrode current collector copper foil with a thickness of 6 μm. The copper foil was dried at 80°C for 8 hours to obtain a negative electrode sheet coated with negative electrode active material layers on both sides.
[0129] After cold pressing and slitting, the material was dried under vacuum at 80℃ for 8 hours to obtain a 4.2mm × 5.2mm negative electrode sheet. The single-sided coating mass of the negative electrode active material layer was 6.5 mg / cm². 2 The compaction density of the negative electrode sheet is 1.7 g / cm³. 3 .
[0130] <Preparation of the positive electrode>
[0131] The positive electrode active material lithium cobalt oxide, the positive electrode conductive agent single-walled carbon nanotubes, and the positive electrode binder polyvinylidene fluoride were mixed in a mass ratio of 96:0.5:3.5. N-methylpyrrolidone was added as a solvent and stirred evenly to prepare a positive electrode slurry.
[0132] The positive electrode slurry was uniformly coated onto both surfaces of an 8 μm thick aluminum foil used as a positive electrode current collector, and then dried at 80°C to obtain a positive electrode sheet coated with positive electrode active material on both sides. After cold pressing and slitting, it was dried under vacuum at 80°C for 8 hours to obtain a 4 mm × 5 mm positive electrode sheet. The single-sided coating mass of the positive electrode active material layer was 19.5 g / cm³. 2 The compaction density of the positive electrode sheet is 4.0 g / cm³. 3 .
[0133] <Preparation of Electrolyte>
[0134] In a dry argon atmosphere glove box, the organic solvents ethylene carbonate and propylene carbonate are mixed at a mass ratio of 1:1, and then lithium salt lithium hexafluorophosphate is added. After mixing evenly, an electrolyte is obtained.
[0135] Based on the mass of the electrolyte, the lithium salt content is 12% by mass, with the remainder being organic solvent.
[0136] <Septum>
[0137] Polypropylene with a thickness of 12μm was used as the diaphragm.
[0138] <Preparation of Lithium-ion Batteries>
[0139] The positive electrode, separator, and negative electrode prepared above are stacked in sequence, with the separator positioned between the positive and negative electrode to act as an isolation layer. The positive electrode, separator, and negative electrode are stacked in 8 layers to obtain the electrode assembly.
[0140] After welding the tabs, the electrode assembly is placed in an aluminum-plastic film packaging bag and dried in an 80°C vacuum oven for 12 hours to remove moisture. The prepared electrolyte is then injected, and the lithium-ion battery is obtained through processes such as vacuum sealing, standing, formation (0.1C constant current charging to 3.4V, then 1C constant current charging to 4.2V), degassing, and edge trimming.
[0141] Examples 1-2 to Examples 1-5, Comparative Examples 1 to Comparative Examples 4
[0142] Except for adjusting the relevant parameters according to Table 1, the rest is the same as in Example 1-1.
[0143] In Examples 1-1 to 1-5, the Young's modulus E0 of the negative electrode active material layer was adjusted by adjusting the Young's modulus E1 and E2 of the first and second negative electrode active materials.
[0144] The silicon-carbon material used in this embodiment is a silicon-carbon material on which silicon is deposited on a carbon skeleton. Its expansion rate is mainly affected by the mass percentage of silicon in the silicon-carbon material, and its Young's modulus is mainly affected by the mass percentage of silicon, the strength of the carbon skeleton, and the porosity of the carbon skeleton. The Young's modulus and expansion rate of the MCMB material are mainly affected by the material processing technology. In this embodiment, silicon-carbon materials with different carbon skeleton strengths are selected, thereby obtaining different Young's moduli E1 of the first negative electrode active material and different Young's moduli E2 of the second negative electrode active material, and thus obtaining negative electrode active material layers with different Young's moduli E0.
[0145] In Comparative Example 3, graphite was used as the second negative electrode active material, while in Comparative Example 4, the same silicon-carbon material as in Examples 1-1 was used as the second negative electrode active material. Examples 2-1 to 2-8
[0146] Except for adjusting the relevant parameters according to Table 2, the rest is the same as in Example 1-1.
[0147] In this embodiment, the same first and second negative electrode active materials as in Example 1-1 are used. The Young's modulus E0 of the negative electrode active material layer is changed by adjusting the mass percentages W1 and W2 of the first and second negative electrode active materials in the negative electrode active material layer. The total mass of the negative electrode active material layer and the mass percentage of the negative electrode active material remain unchanged.
[0148] Examples 3-1 to 3-4
[0149] Except for adjusting the relevant parameters according to Table 3, the rest is the same as in Example 1-1.
[0150] Examples 4-1 to 4-4
[0151] Except for adjusting the relevant parameters according to Table 4, the rest is the same as in Example 1-1.
[0152] Examples 5-1 to 5-11
[0153] Except for adjusting the relevant parameters according to Table 5, the rest is the same as in Example 1-1.
[0154] In Examples 5-2 to 5-5, the same silicon-carbon material as in Example 1-1 was used, only the mass percentage of silicon was adjusted to 30%, 45%, 55%, and 60%, respectively. In Example 5-1, the first negative electrode active material was a silicon-oxygen material, specifically SiO₂. 1.2 The silicon-oxygen material is composed of silicon and oxygen elements, and the atomic ratio of silicon to oxygen in the silicon-oxygen material is 1:1.2. The silicon-carbon material used in the first negative electrode active material of Examples 5-7 to 5-11 is the same as that in Examples 1-1, wherein the mass percentage of silicon element is 50% based on the mass of the silicon-carbon material. The first negative electrode active material used in Examples 5-9 is micron-sized silicon and silicon-carbon material, wherein the mass percentage of micron-sized silicon is 30% based on the mass of the first negative electrode active material, and the mass percentage of silicon-carbon material (wherein the mass percentage of silicon element is 50% based on the mass of the silicon-carbon material) is 70%. The first negative electrode active material used in Examples 5-10 is the same SiO as in Example 5-1. 1.2 And the same silicon-carbon material as in Examples 1-1, wherein the SiO2 content is based on the mass of the first negative electrode active material. 1.2 The mass percentage of silicon-carbon material is 50%, and the mass percentage of silicon element is 50% based on the mass of silicon-carbon material; in Examples 5-11, the second negative electrode active material is MCMB and lithium titanate, and the mass percentage of MCMB and lithium titanate is 50% based on the mass of the second negative electrode active material.
[0155] Examples 6-1 to 6-8
[0156] Except for adjusting the relevant parameters according to Table 6, the rest is the same as in Example 1-1.
[0157] In Examples 6-1 to 6-8, negative electrode binders with different film elongation ratios were obtained by adjusting the type and molecular weight of the negative electrode binder.
[0158] The raw material composition and test data of different embodiments and comparative examples are shown in Tables 1-6 below.
[0159] Table 1
[0160]
[0161]
[0162] The test results above show that, compared with Comparative Examples 1-4, the batteries prepared in this application have higher specific capacity and capacity retention of the material layer, and lower expansion rate. Comparative Example 1 has an excessively low E0, making it difficult to resist the expansion of the silicon-containing material during cycling. The silicon-containing material is prone to electrical connection failure, reducing the specific capacity of the material layer and affecting cycle performance. Comparative Example 2 has an excessively high E0, making the silicon-carbon material brittle and prone to breakage during cycling. This damages the conductive network of the negative electrode material layer, reducing the specific capacity of the material layer and affecting cycle performance and expansion rate. Comparative Example 3 uses graphite as the second negative electrode active material. Graphite has an excessively low E2, making it susceptible to irreversible deformation under pressure. During battery cycling, it cannot maintain a tight connection with the silicon-carbon material, resulting in a significant decrease in the specific capacity of the material layer. This not only significantly reduces cycle performance but also fails to suppress the expansion of the silicon-carbon material, leading to a high battery expansion rate. Figure 1 and Figure 2 SEM images of the negative electrode sheets prepared in Examples 1-1 and Comparative Example 3 of this application are shown respectively. Figure 1 It can be seen that the second negative electrode active material MCMB (the blackish-gray material in the figure), which has a high E2, remains tightly bonded to the silicon-carbon material (the white material in the figure) after cold pressing, but from... Figure 2 As can be seen, in Comparative Example 3, graphite (the blackish-gray material in the figure) is used as the second negative electrode active material. The graphite's E2 is too low, and irreversible deformation occurs after cold pressing. It cannot maintain a tight connection with the first negative electrode active material, silicon-carbon material (the white material in the figure). In subsequent cycles, due to the large volume expansion of silicon-carbon material, the stress released by the expansion causes the graphite material with the low E2 to deform, further weakening the connection between the graphite material and silicon-carbon material. This is not conducive to the specific capacity of the material layer and leads to a decrease in cycle performance. In Comparative Example 4, silicon-carbon material is used as the second negative electrode active material. The E2 is too high, which leads to a corresponding increase in E0 and a high expansion rate α2. Although this increases the specific capacity of the material layer, the large expansion and contraction of silicon-carbon material during cycling significantly reduces cycle performance and significantly increases the battery expansion rate. By setting 40GPa≤E0≤80GPa and 30GPa≤E2≤50GPa, the second negative electrode active material can resist the expansion of the first negative electrode active material, so that the negative electrode active materials can maintain their integrity and electrical connection during cycling, thereby obtaining a higher specific capacity and capacity retention rate of the material layer, and a lower expansion rate.
[0163] Table 2
[0164]
[0165]
[0166] The test results above show that, compared with Examples 1-1, Examples 2-1, 2-2, 2-3, and 2-4 have smaller W1 / W2 ratios, lower silicon content in the negative electrode active material layer, and smaller expansion and contraction of the negative electrode active material during cycling. Therefore, they have better cycle performance and lower expansion rate, but lower specific capacity of the material layer. Examples 2-7 and 2-8 have larger W1 / W2 ratios, higher silicon content in the negative electrode active material layer, and larger expansion during cycling, leading to electrical connection failure and damage to the conductive network. Although they have higher specific capacity of the material layer, the cycle performance and expansion performance of the battery are poor. By setting 0.25≤W1 / W2≤4, especially 0.5≤W1 / W2≤2, it is beneficial to control the expansion and contraction rate of the negative electrode active material during cycling, making it easier for the conductive network of the negative electrode active material layer to maintain electrical connection during cycling, and achieving a higher specific capacity of the material layer.
[0167] Table 3
[0168]
[0169]
[0170] The test results above show that, compared with Examples 1-1, the D2 / D1 ratio in Example 3-1 is too large, and the D2 / D1 ratio in Example 3-4 is too small. This leads to a mismatch in the average particle size of the two negative electrode active materials, resulting in uneven dispersion of the active materials in the negative electrode active material layer. Consequently, this leads to uneven local current density distribution within the negative electrode sheet, accelerating capacity decay and significantly reducing the battery's cycle performance. By setting 0.75≤D2 / D1≤1.25, the average particle size of the two negative electrode active materials is matched, which helps increase the contact between particles, improves the stability and integrity of the negative electrode sheet structure, enhances the specific capacity of the material layer, improves the battery's capacity retention rate, and reduces the expansion rate.
[0171] Table 4
[0172]
[0173]
[0174] The test results above show that, compared with Examples 1-1, the excessively small D1 in Example 4-1 leads to increased side reactions, deterioration of cycle performance and battery expansion rate. In Example 4-4, the excessively large D1 affects the kinetic performance of the negative electrode, resulting in difficulty in lithium removal and decreased cycle performance. By setting 4μm≤D1≤12μm, the average particle size of the negative electrode active material is kept within a suitable range, facilitating lithium-ion transport while reducing side reactions, thereby improving battery capacity retention and controlling expansion.
[0175] Table 5
[0176]
[0177]
[0178] Note: The silicon content of the silicon-carbon material used in Example 5-2 was 30% by mass; the silicon content of the silicon-carbon material used in Example 5-3 was 45% by mass; the silicon content of the silicon-carbon material used in Example 5-4 was 55% by mass; and the silicon content of the silicon-carbon material used in Example 5-5 was 60% by mass.
[0179] The test results above show that, compared with Examples 1-1, Examples 5-1 to 5-10 used different first negative electrode active materials. Among them, compared with the examples using silicon-carbon and silicon-oxygen materials, Examples 5-6 and 5-9, which used micron-sized silicon, significantly improved the specific capacity of the material layer. However, due to the high specific capacity but poor stability of micron-sized silicon, the battery expansion rate was high and the cycle performance was somewhat reduced. Examples 5-7 and 5-11 used lithium titanate as the second negative electrode active material in whole or in part. The cycle performance and expansion performance of the battery were maintained at a good level. However, due to the low specific capacity of lithium titanate itself, the specific capacity of the material layer was limited.
[0180] Table 6
[0181]
[0182]
[0183] The test results above show that, compared with Examples 1-1, the molecular weight of the negative electrode binder used in Example 6-1 is too low, resulting in a low film stretch ratio and low tensile mechanical properties of the negative electrode active material layer. Although a lower stretch ratio provides stronger binding to the active material, insufficient stretch ratio can lead to breakage, easily damaging the bonding network and consequently the conductive network. Therefore, cycle performance significantly decreases and expansion rate increases. In Example 6-4, silicone rubber was used as the negative electrode binder, resulting in an excessively high film stretch ratio. This resulted in high tensile mechanical properties of the negative electrode active material layer, but the high ion transport impedance made lithium removal difficult, leading to decreased cycle performance. By setting the film stretch ratio of the negative electrode binder to 40%–500%, the negative electrode active material is better bound while facilitating lithium ion transport. This results in higher integrity of the bonding network during cycling, good conductivity of the conductive network, improved battery capacity retention, and reduced expansion. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them; under the concept of this application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of this application as described above, which are not provided in detail for the sake of brevity; although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector, wherein the Young's modulus of the negative active material layer is E0 and satisfies: 40GPa≤E0≤80GPa; The negative electrode active material layer comprises a first negative electrode active material and a second negative electrode active material, wherein the Young's modulus of the second negative electrode active material is E2 and satisfies: 30GPa≤E2≤50GPa.
2. The negative electrode sheet according to claim 1, characterized in that, Based on the total mass of the negative electrode active materials, the mass percentage of the first negative electrode active material is W1, the mass percentage of the second negative electrode active material is W2, and the following condition is met: 0.25≤W1 / W2≤4.
3. The negative electrode sheet according to claim 2, characterized in that, The condition W1 and W2 satisfy: 0.5≤W1 / W2≤2.
4. The negative electrode sheet according to claim 1, characterized in that, The average particle size of the first negative electrode active material is D1, and the average particle size of the second negative electrode active material is D2, and the following condition is met: 0.75≤D2 / D1≤1.
25.
5. The negative electrode sheet according to claim 4, characterized in that, The conditions D1 and D2 satisfy: 4μm≤D1≤12μm, and / or 3μm≤D2≤15μm.
6. The negative electrode sheet according to claim 1, characterized in that, 25%≤W1≤80%。 7. The negative electrode sheet according to claim 6, characterized in that, The first negative electrode active material is one or more of silicon-carbon materials, silicon-oxygen materials, and elemental silicon materials.
8. The negative electrode sheet according to claim 1, characterized in that, The second negative electrode active material is selected from MCMB and / or lithium titanate.
9. The negative electrode sheet according to claim 1, characterized in that, The negative electrode active material layer also includes a negative electrode binder, and the film elongation of the negative electrode binder is 40% to 500%.
10. The negative electrode sheet according to claim 9, characterized in that, The negative electrode binder is selected from one or more of styrene-butadiene rubber, polyurethane, polyimide, polyamide-imide, polyvinylidene fluoride, and polyvinylbenzene.
11. An electrochemical device, characterized in that, It includes a positive electrode, a separator, an electrolyte, and a negative electrode according to any one of claims 1 to 10, wherein the separator is located between the positive electrode and the negative electrode.
12. An electronic device comprising the electrochemical device as claimed in claim 11.